Relación entre el control interno y la rentabilidad de las empresas turísticas en la región de Loreto, periodo 2022 - Ramirez Soria, Wendy Valeria (2024)
This research examines the relationship between internal control and profitability of tourism companies in the Loreto Region. Using a quantitative approach and a correlational design, data from 242 workers were analyzed to evaluate how the implementation of internal controls affects business profitability. Using Spearman's correlation coefficient, a moderate positive correlation was found (Rho=0.389, p-value=0.036), indicating that robust internal control practices may be associated with increases in profitability. Additionally, a positive correlation was identified between the quality of the risk assessment and the return on investment (Rho=0.302, p-value=0.033), and between the level of controls implemented and the net profit margin (Rho=0.312 , p-value=0.045). These findings support theories that suggest that effective internal controls and good risk management are crucial to the financial health of companies. The research contributes to the existing body of knowledge by highlighting the importance of internal management in the economic performance of the tourism sector and offers practical recommendations for continuous improvement in the internal control and profitability of companies in this dynamic region.